ANALISIS PENGENDALIAN INTERN SISTEM PENERIMAAN DAN PENGELUARAN KAS DALAM MENINGKATKAN KUALITAS LAPORAN ARUS KAS - Anggraeni, Neng Hany; Suarsa, Abin; Verawaty, Verawaty (2017)
Cash receipts and expenditure controlling are important in a company, because cash it self is the most important assets account, that also has an important position in funding company operations.In analyzing some data, the writer using qualitative method. Using both primary and secondary data. This research collecting data technique using field research with interview, observation, and documentations.The examp results showing that internal cash receipts controlling has been effective enough,contraty with the internal expenditure cash controlling system. In cash disbursment system a writer still found some factors than wasn’t fully work yet. Such as double function beetween receiving, storing, and cash register. There still no function splitting between cash and petty cash. Cash on hand and cash register are both uninsured. Klinik Utama Bandung Eye Center in general already compile cash flow report based on PSAK No. 2, that compile report with indirect method.